1991
DOI: 10.1007/bf01876812
|View full text |Cite
|
Sign up to set email alerts
|

A cytogenetic survey of 14,835 consecutive liveborns

Abstract: SummaryThe results of chromosome studies on cultured umbilical cord blood lymphocytes from a consecutive series of 14,835 liveborn infants (7,608 males and 7,227 females) are described. Ninety-three infants (6.27 per 1,000) had a m~or chromosome abnormality. Of these, thirtyone infants (2.09 per 1,000) had sex chromosome abnormalities. Seven male infants had a 47,XXY karyotype, five had a 47,XYY karyotype, and three were mosaics. One male had a ring Y chromosome in all cells examined. A pericentric inversion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 11 publications
3
39
1
Order By: Relevance
“…When taken separately, the frequency of these abnormalities does not statistically differ from that observed in 11 680, 3993 and 34 910 newborns by Jacobs et al (1974) (P = 0.35), Buckton et al (1980) (P = 0.92) and Nielsen and Wohlert (1991) (P = 0.58), respectively. The difference is, however, significant when comparing our results to those obtained by Hamerton et al (1975) (P = 0.04), Hansteen et al (1982) (P = 0.03) and Maeda et al (1991) (P = 0.02) in 13 939, 1830 and 14 835 children at birth, respectively.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…When taken separately, the frequency of these abnormalities does not statistically differ from that observed in 11 680, 3993 and 34 910 newborns by Jacobs et al (1974) (P = 0.35), Buckton et al (1980) (P = 0.92) and Nielsen and Wohlert (1991) (P = 0.58), respectively. The difference is, however, significant when comparing our results to those obtained by Hamerton et al (1975) (P = 0.04), Hansteen et al (1982) (P = 0.03) and Maeda et al (1991) (P = 0.02) in 13 939, 1830 and 14 835 children at birth, respectively.…”
Section: Discussioncontrasting
confidence: 52%
“…Large-scale studies focusing on the prevalence of both balanced and unbalanced chromosomal abnormalities in humans have been realized within unselected newborn populations (Jacobs et al, 1974;Hamerton et al, 1975;Buckton et al, 1980;Hansteen et al, 1982;Maeda et al, 1991;Nielsen and Wohlert, 1991). On the contrary, the frequency of chromosomal aberrations in adults has been established only in cases of couple infertility (Van Assche et al, 1996;Gekas et al, 2001;Vincent et al, 2002) or recurrent spontaneous miscarriages (Fryns and Van Buggenhout, 1998), mainly because ethical and practical reasons make large-scale cytogenetic studies in normal adults difficult to set up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since cytogenetic abnormalities prenatally diagnosed by amniocentesis show a higher rate of spontaneous abortion and/or stillbirth than cytogenetically normal fetuses (Hook 1983;Hook et al 1988Hook et al , 1989Halliday et al 1995;Macintosh et al 1995), the incidence at prenatal testing is markedly different from that at live birth. Compared to the previous reports of nonmosaic aneuploidies diagnosed in live births (Hook et al 1984;Mutton et al 1991), the abnormal karyotypes and their order revealed in this study were almost the same, with some exceptions, but the incidences of each nonmosaic aneuploidy were markedly higher; for example, the incidence of trisomy 21 in Japan is 1.42␣ /␣ 1000 live births (Maeda et al 1991). These higher incidences may be caused by selective miscarriage occurring during the second or third trimester of pregnancy, and the fetus with the aneuploidy may be stillborn.…”
Section: Discussionmentioning
confidence: 46%
“…However, a recent Belgian study described a significantly higher prevalence of Klinefelter syndrome among male-to-female GD [184] than expected, based on the population data [185]. In addition, a recent study showed the presence of higher dysphoric symptoms in Klinefelter persons compared to a group of healthy controls [186].…”
Section: Xxy Klinefelter Syndrome and Variants Men Withmentioning
confidence: 89%